O ENSINO DE MATEMÁTICA PARA PRIVADOS DE LIBERDADE: um estudo da política estadual de educação do Maranhão. - SANTOS, Helismar Medeiros dos (2021)
This work is a study of the State Policy for Education in Prisons in Maranhão. We aim to investigate the educational practices that are developed in Prison Resocialization Units (UPR), especially those linked to the teaching of Mathematics, in order to understand how these practices influence the resocialization of people deprived of freedom. Thus, we intend to answer the following question: how are educational practices organized in the UPR of Maranhão and how does the teaching of Mathematics contribute to the resocialization of people deprived of liberty? In order to reach our goal, we started with a qualitative approach that allowed us to collect and analyze documents and interviews that served as a theoretical basis for the development of this research. Among the analyzed material, we emphasize those of state origin, such as the State Plan for Education in Maranhão Prisons (2015) and the EJA Newsletter (2021), which present as strengths: a brief history of the first educational actions developed in these prisons, a pedagogical proposal for teaching, goals related to the construction of schools, hiring teachers and expanding the offer of vacancies, as well as the organization of the curriculum for Basic Education for people deprived of liberty. In addition to consulting the documents, we also conducted interviews with professionals who work in the Prison System of Maranhão, some linked to the State Department of Education, which were examined using Bardan's content analysis. As a result, we found that Maranhão is the state that most promotes educational practices for people deprived of liberty in Brazil and that the State Plan for Education in Prisons has been an important guiding document for these practices. Regarding the teaching of Mathematics, we identified that it is present in most educational practices developed in the UPR, such as in Elementary and High School, in the National Examination for Certification of Skills for Youth and Adults or the National Examination in High School or even in training courses and craft learning, which are linked to resocialization, in addition to which, teachers and other professionals who work in the prison system of Maranhão, recognize that the teaching of Mathematics favors resocialization, since students deprived of freedom need this knowledge to raise their level of schooling, in daily life to develop as citizens and because it is one of the areas of knowledge with the highest number of hours, which makes possible the remission of the sentence for studying.